Peningkatan Literasi Teknologi IoT untuk Mendukung Implementasi Smart City di Masyarakat Perkotaan - Apri Affandi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The implementation of Internet of Things (IoT) technology in the smart city concept has become an important innovation that plays a major role in improving the quality of life of urban communities. IoT enables the integration of various interconnected devices and systems to optimize the management of city resources such as energy, transportation and security. This research aims to encourage the influence of IoT technology on the implementation of smart cities in several cities in Indonesia. Using qualitative and quantitative methods, this research collects data through interviews with city stakeholders as well as secondary data analysis from related reports and publications. The research results show that the application of IoT in smart cities has a significant impact on increasing operational efficiency, better environmental management, and improving public services. However, this research also found a number of challenges, such as limited infrastructure, data security problems, and low digital literacy among the public. In conclusion, although IoT has great potential in accelerating the implementation of smart cities, policies are needed that support and increase society's capacity to reach the full potential of this technology.